Histopathological Findings Predict Renal Recovery in Severe ANCA-Associated Vasculitis Requiring Intensive Care Treatment - Hakroush, Samy; Tampe, Desiree; Korsten, Peter; Ströbel, Philipp; Zeisberg, Michael; Tampe, Björn (Frontiers in Medicine, 2021)
Renal involvement is a common and severe complication of AAV as it can cause ESRD. Histopathological subgrouping and ARRS are helpful to predict long-term ESRD in patients with AAV. Because a subgroup of critically ill patients with severe AAV present with deterioration of kidney function requiring dialysis at admission, we here aimed to evaluate histopathological findings and predictive value of Berden’s histopathological subgrouping and ARRS for svererity of AKI and requirement of RRT during short-term clinical course in critically ill patients requiring intensive care treatment and predictors for short-term renal recovery in patients requiring RRT. A subgroup of 15/46 (32.6%) AAV patients with biopsy-proven AAV required RRT during short-term course of disease, associated with requirement of critical care treatment. While histopathological subgrouping and ARRS were associated with requirement of acute RRT, presence of global glomerular scarring was the strongest predictor of failure to recover from RRT after initiation of remission induction therapy. This new aspect requires further investigation in a prospective controlled setting for therapeutic decision making especially in this subgroup.